Cellulose nanofibrils and nano-scaled titanium dioxide-reinforced biopolymer nanocomposites: Selecting the best nanocomposites with multicriteria decision-making methods - Gumus, Havva; Aydemir, Deniz; Altuntas, Ertugrul; Kurt, Rıfat; İmren, Erol; Kurt, Rıfat; İmren, Erol; Aydemir, Deniz (Sage Publications Ltd, 2020)
The aim of the paper is to determine the effects of nano fillers such as cellulose nanofibrils and nano-scaled titanium dioxide on some properties of polyhydroxybutyrate and polylactic acid biopolymers; it also determined the selection of biopolymer nanocomposites with the optimum properties by using multicriteria decision-making methods such as multi-attribute utility theory, simple additive weighting, and weighted aggregated sum product assessment. Test results showed that the mechanical properties of the biopolymer nanocomposites generally increased with the addition of the cellulose nanofibrils and nano-scaled titanium dioxide. However, the addition of nano-scaled titanium dioxide decreased the tensile modulus. The addition of the cellulose nanofibrils had a higher effect on the tensile and flexure modulus of elasticity than the addition of the nano-scaled titanium dioxide. Thermal properties were generally found to improve with the addition of the cellulose nanofibrils and nano-scaled titanium dioxide. Melting temperature (T-m) generally decreased with the addition of the nano fillers. The scanning electron microscopic images showed that the nano fillers were dispersed as white dots in the biopolymer matrix. After accelerated weathering and decay test, outdoor performance of the biopolymer nanocomposites was found to be improved with the addition of the nano fillers. Multicriteria decision-making methods were conducted to determine the biopolymer nanocomposites having the optimum properties, and all the methods showed that the best biopolymer nanocomposites was polylactic acid with 1% cellulose nanofibrils.
Keywords: Biopolymers; Nano Fillers; Multicriteria Decision-Making Methods; Material Characterization